Filipino in the Computer Age: Concept in Computer Word Translation - Valdepeñas, Dyan (International Journal of Arts, Sciences and Education, 2024)
A big challenge for the Filipino national Language isa the arrival of the computer age or the “cyber world” that uses “cyber language”. Its specific purpose is to address what is the concept of teachers and student in relation to computer translations used in translation and the technical and communicative translation method is the main preference for computer word translation agreed by teachers and students. This study covers all teacher teaching computer at Isabela State University, Cabagan campus and fourth year students taking computer subject. This study was limited to the self-concept of teachers and students in computer translations conducted by the researcher through technical and communicative translation. Keywords: Filipino sa Computer Age, Konsepto, pagsasaling komunikatibo, pagsasaling teknikal, saling salitang computer